(Tables 3, 4) Age models of ODP Leg 138 sites - Shackleton, Nicholas J; Baldauf, Jack G; Flores, José-Abel; Iwai, Masao; Moore, Theodore C; Raffi, Isabella; Vincent, C (Supplement to: Shackleton, NJ et al. (1995): Biostratigraphic summary for Leg 138. In: Pisias, NG; Mayer, LA; Janecek, TR; Palmer-Julson, A; van Andel, TH (eds.), Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 138, 517-536, https://doi.org/10.2973/odp.proc.sr.138.127.1995, 1995)
The sediments recovered during Leg 138 have provided us with a remarkable opportunity to improve the stratigraphic framework for east-central Pacific Ocean Neogene age sediments. In this chapter, we review some of the data that have been generated and derive best estimates for the ages of potentially useful biostratigraphic datums, within the paleomagnetic temporal framework of Shackleton et al. determined for this volume and also, for comparison, according to the 1985 and 1992 paleomagnetic time scales of Berggren et al. and Cande and Kent, respectively.